Isovolumic contraction time of right ventricle in d-transposition of great arteries. - Fouron, J C (1980)
The pre-ejection period of the right ventricle in d-transposition of the great arteries is known to be prolonged, compared with the same interval of the left ventricle of normal subjects. In the present study, the echocardiographic measurement of the components of the pre-ejection period of the right ventricle of 14 patients with d-transposition of the great arteries shows that the isometric contraction time of the right ventricle in d-transposition of the great arteries is similar to the same interval calculated on the left ventricle of 76 normal children of comparable age. On the other hand, the electromechanical delay was significantly greater for the right ventricle of d-transposition of the great arteries than for the left ventricle of the normal subjects. It is concluded that the prolonged pre-ejection period of the right ventricle in d-transposition of the great arteries is not the result of right ventricular dysfunction but solely of a longer electromechanical delay.